Penilaian Bahasa Isyarat Baharu Untuk Pengajaran Dan Pembelajaran Solat Bagi Orang Pekak - Siti Ramna Khamaruddin; Nurul Asiah Fasehah Muhamad; Norakyairee Mohd. Raus; Adnan Mohamed Yusoff; Mahyuddin Hashim; Noornajihan Ja‘afar; Mohd Nur Adzam Rasdi (Universiti Sains Islam Malaysia, 2024)
The sign language is the main language used in the teaching and learning approach (PnP) of solat (prayer) for deaf people. However, there have been sign language confusions in terms of form and the true meaning of the term. This is because the signs are developed based on the custom and understanding of the deaf. Hence, this study evaluates new sign language developed to ensure the process (PnP) of solat (prayer) for the deaf can be carried out more effectively. This study utilises Cohen Kappa for analysis of the evaluation of five experts from the field of religion and six from the field of sign language. In addition, a qualitative approach through group interviews is also conducted to enrich the findings. Based on the findings of the study, this evaluation has achieved the Cohen Kappa Coefficient Index at 0.87 level, which is at an excellent scale level for the whole new sign language developed. In terms of implication, this evaluation can provide a sign language parallel to the religious meaning and understanding of the deaf in Malaysia in (PnP) solat.